Research Trends on Promoting Mental Health and Resilience Literacy through Children's Literature - Thoyib, Muhammad Edy; Kusuma, Agung Wiranata (Universitas Gadjah Mada, 2025)
This study examines research trends on promoting mental health literacy in children’s literature throughbibliometric analysis. With growing recognition of children’s mental health as a critical issue, literature has emerged as a valuable tool to foster emotional resilience and well-being. This study aims to identify emerging themes and shifts in focus, ensuring future studies address the most pressing mental health concerns in children’s literature. Additionally, mapping these trends highlights under-researched areas, guiding targeted investigations to strengthen evidence-based interventions and support for children. This study employed data from Scopus and found seven eligible publications between 2015 and 2024. To comprehensively analyze the collected data, VOSviewer is applied to capture co-authorship networks, keyword co-occurrences, and thematic clusters. The results highlight a rise in publications during the COVID-19 pandemic, reflecting increased global attention to mental health. The United States leads research output, followed by China and the United Kingdom, though cross-institutional collaborations remain limited. Prominent themes include resilience, emotional intelligence, and the impact of bullying, with emerging topics like digital interventions and bibliotherapy. However, areas such as the experiences of foster children and those facing cyberbullying are underexplored. The study underscores the need for interdisciplinary approaches and international partnerships to address these gaps. Fragmented research themes highlight the importance of broader integration. By promoting emotional literacy and resilience, children’s literature holds significant potential to support mental health initiatives, offering valuable insights for future research and practical applications.